2020
DOI: 10.1093/ve/veaa095
|View full text |Cite
|
Sign up to set email alerts
|

Divergent RNA viruses in Macrophomina phaseolina exhibit potential as virocontrol agents

Abstract: Macrophomina phaseolina is an important necrotrophic phytopathogenic fungus and cause extensive damage in many oilseed crops. Twelve M.phaseolina isolates with diverse biological phenotypes were selected for a high-throughput sequencing-based metatranscriptomic and bioinformatics analysis to identify viruses infecting M.phaseolina . The analysis identified 40 partial or nearly complete viral genome segments, 31 of which were novel viruses. Among these vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 75 publications
(75 reference statements)
0
28
0
Order By: Relevance
“…The 5'-UTR is with 757 nt much longer than the 3'-UTR of 45 nt length. However, a protein search at CDD confirmed that the predicted ORF2 protein contains a RdRp domain (RdRp_4; pfam02123; Cd length: 465), exhibiting conserved motif characteristics detected in members of the proposed Fusagraviridae members in former studies (e.g., Fusarium poae dsRNA virus 2 and 3 [13], Trichoderma asperellum dsRNA virus 1 [55], or Macrophomina phaseolina fusagravirus 2-5 [56]), but also in other dsRNA viral families, such as Colletotrichum fructicola chrysovirus 1 [57] or Macrophomina phaseolina chrysovirus 2 RNA1 [56]. The similarity in the RdRp region supported additionally that the M10544-dsRNA is a dsRNA fusagravirus.…”
Section: Dsrna Represents a Non-segmented Genome Of A Novel Virus Encoding The Conserved Rdrp Domainmentioning
confidence: 88%
See 2 more Smart Citations
“…The 5'-UTR is with 757 nt much longer than the 3'-UTR of 45 nt length. However, a protein search at CDD confirmed that the predicted ORF2 protein contains a RdRp domain (RdRp_4; pfam02123; Cd length: 465), exhibiting conserved motif characteristics detected in members of the proposed Fusagraviridae members in former studies (e.g., Fusarium poae dsRNA virus 2 and 3 [13], Trichoderma asperellum dsRNA virus 1 [55], or Macrophomina phaseolina fusagravirus 2-5 [56]), but also in other dsRNA viral families, such as Colletotrichum fructicola chrysovirus 1 [57] or Macrophomina phaseolina chrysovirus 2 RNA1 [56]. The similarity in the RdRp region supported additionally that the M10544-dsRNA is a dsRNA fusagravirus.…”
Section: Dsrna Represents a Non-segmented Genome Of A Novel Virus Encoding The Conserved Rdrp Domainmentioning
confidence: 88%
“…This study revealed that 13/31 (c. 40%) of C. naterciae strains harbour a unique dsRNA virus named Cryphonectria naterciae fusagravirus 1 (CnFGV1). The complete CnFGV1-genome derived from strain M10544 consists of 10,161 nt, which possesses two ORFs-ORF1 and ORF2-of which ORF2 is situated in -1 frame relative to ORF1, as found for many other dsRNA mycoviruses within the order Ghabrivirales [13,[55][56][57][58][59]61]. Amino acid sequence analyses showed moderate levels of sequence identity of ORF1 and ORF2 to the counterparts of dsRNA viruses such as Fusarium virguliforme dsRNA mycovirus [58] and Trichoderma atroviride mycovirus [59] of the previously proposed viral family Fusagraviridae.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mycovirus-induced hypovirulence could be found in many important plant hemi-biotrophic and necrotrophic pathogenic fungi, including Aspergillus spp., Alternaria alternata , Bipolaris maydis , Botryosphaeria dothidea , Botrytis spp., Cryphonectria parasitica , Colletotrichum spp., Diaporthe spp., Fusarium spp., Helicobasidium mompa , Helminthosporium victoriae , Heterobasidion annosum , Macrophomina phaseolina , Magnaporthe oryzae , Ophiostoma spp., Penicillium digitatum , Pestalotiopsis theae , Rosellinia necatrix , Rhizoctonia solani , Sclerotinia spp. and so on [ 3 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ], indicating hypovirulence-related mycoviruses as potential resources to control plant fungal diseases [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sometimes, lab isolates of fungal cultures have sectoring growth and are discarded by the pathologists when the transferred isolates grow slowly and become hard to maintain. Therefore, candidates of biopesticide or biotechnological use could be eliminated in the culturing/serial passage process, e.g., Macrophomina phaseolina tobamo -like virus 1 [ 11 , 14 ]. Moreover, some fungal pathogens, e.g., sunflower downy mildew and rust, being obligate parasites, cannot be cultured in the lab.…”
Section: Introductionmentioning
confidence: 99%